Phylogenetic comparative analysis: Chemical and biological features of caseins (alpha-S-1, alpha-S-2, beta- and kappa-) in domestic dairy animals - Hassanin, Abdallah A.; Osman, Ali; Atallah, Osama Osman; El-Saadony, Mohamed T.; Abdelnour, Sameh A.; Taha, Heba S. A.; Awad, Mohamed F.; Elkashef, Hany; Ahmed, Ahmed Ezzat; Abd El-Rahim, Ibrahim; Mohamed, Abdullah; Eldomiaty, Ahmed S. (Frontiers in Veterinary Science, 2022)
Caseins determine the physicochemical, physiological, and biological characteristics of milk. Four caseins—alpha-S-1, alpha-S-2, beta, and kappa—were analyzed phylogenetically and in silico and characterized regarding chemical, antimicrobial, and antioxidant features in five dairy animals: Arabian camels, sheep, goats, cattle, and water buffalos. The sequence of full-length amino acids of the four caseins for the five species was retracted from the NCBI GenBank database. Multiple sequence alignment is used to examine further the candidate sequences for phylogenetic analysis using Clustal X and NJ-Plot tools. The results revealed that sheep and goats possess strong similarities (98.06%) because of their common ancestor. The same was observed with cattle and water buffalos (96.25%). The Arabian camel was located in a single subclade due to low similarity in casein residues and compositions with other dairy animals. Protein modeling showed that alpha-S1- and alpha-S2-caseins possess the highest number of phosphoserine residues. The in silico computed chemical properties showed that β-casein recorded highest hydrophobicity index and lowest basic amino acid content, while α-S2-casein showed the opposite. The computed biological parameters revealed that α-S2-casein presented the highest bactericidal stretches. Only Arabian camel β-casein and k-casein showed one bactericidal stretches. The analysis also revealed that β-casein, particularly in Arabian camels, possesses the highest antioxidant activity index. These results support the importance of the bioinformatics resources to determine milk casein micelles' chemical and biological activities.